Physicochemical properties of respirable-size lunar dust. (February 2015) - McKay, D.S.; Cooper, B.L.; Taylor, L.A.; James, J.T.; Thomas-Keprta, K.; Pieters, C.M.; Wentworth, S.J.; Wallace, W.T.; Lee, T.S.
Abstract: We separated the respirable dust and other size fractions from Apollo 14 bulk sample 14003, 96 in a dry nitrogen environment. While our toxicology team performed in vivo and in vitro experiments with the respirable fraction, we studied the size distribution and shape, chemistry, mineralogy, spectroscopy, iron content and magnetic resonance of various size fractions. These represent the finest-grained lunar samples ever measured for either FMR np-Fe 0 index or precise bulk chemistry, and are the first instance we know of in which SEM/TEM samples have been obtained without using liquids. The concentration of single-domain, nanophase metallic iron (np-Fe 0 ) increases as particle size diminishes to 2 µm, confirming previous extrapolations. Size-distribution studies disclosed that the most frequent particle size was in the 0.1–0.2 µm range suggesting a relatively high surface area and therefore higher potential toxicity. Lunar dust particles are insoluble in isopropanol but slightly soluble in distilled water (~0.2 wt%/3 days). The interaction between water and lunar fines, which results in both agglomeration and partial dissolution, is observable on a macro scale over time periods of less than an hour. Most of the respirable grains were smooth amorphous glass. This suggests less toxicity than if the grains were irregular, porous, or jagged, and may account for the fact that lunar dust is less toxic than ground quartz. Highlights: We separated lunar soil particles averaging 2 μm diameter without exposure to air. Our method provides uncompromised samples in many size ranges. Lunar soil agglomerates and starts dissolving upon exposure to water. Our method allows SEM/TEM study of grain surfaces that have not been altered. Respirable lunar soil grains often contain more than one mineral or glass type.